2014
DOI: 10.1371/journal.pone.0102122
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Cutaneous Research Funded by the National Institute of Arthritis and Musculoskeletal and Skin Diseases with 2010 Global Burden of Disease Results

Abstract: ImportanceDisease burden data helps guide research prioritization.ObjectiveTo determine the extent to which grants issued by the National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS) reflect disease burden, measured by disability-adjusted life years (DALYs) from Global Burden of Disease (GBD) 2010 project.DesignTwo investigators independently assessed 15 skin conditions studied by GBD 2010 in the NIAMS database for grants issued in 2013. The 15 skin diseases were matched to their respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Funding will be required to support an increase in scabies research; priority areas include the development of robust diagnostic tests for scabies, and improved treatment and control strategies, particularly in view of the emerging threat of drug resistance. In the USA, funding for scabies research was shown to be under-represented in relation to the associated disease burden, and this gap needs to be addressed [89]. In the UK research and policy efforts should address the management of scabies outbreaks in institutions, with particular focus on the use of oral treatments, such as ivermectin or moxidectin, and increasing the availability of these drugs.…”
Section: Strategy For Scabies Controlmentioning
confidence: 99%
“…Funding will be required to support an increase in scabies research; priority areas include the development of robust diagnostic tests for scabies, and improved treatment and control strategies, particularly in view of the emerging threat of drug resistance. In the USA, funding for scabies research was shown to be under-represented in relation to the associated disease burden, and this gap needs to be addressed [89]. In the UK research and policy efforts should address the management of scabies outbreaks in institutions, with particular focus on the use of oral treatments, such as ivermectin or moxidectin, and increasing the availability of these drugs.…”
Section: Strategy For Scabies Controlmentioning
confidence: 99%
“…[1][2][3][4] GBD facilitates epidemiologic comparison of disease burden. 5,6 Fifteen skin conditions are represented in the study along with a category for ''other skin and subcutaneous diseases.'' Before GBD 2010, in 1998, the Institute of Medicine (IOM) urged the National Institutes of Health (NIH) to correlate burden of disease with US funding distribution.…”
mentioning
confidence: 99%
“…11 A further analysis of how skin disease burden in the 2010 surveys was matched by research funding from the US National Institutes of Health indicated that some diseases such as dermatitis and NMSC were well matched, whereas others such as cellulitis, pressure ulcers, urticaria, acne, viral and fungal diseases, scabies, and melanoma were less well represented. 772 A similar pattern of under-representation was evident for systematic reviews published by The Cochrane Collaboration. Measurement of skin disease burden using disability-adjusted life-year metrics allows comparison with other diseases.…”
Section: Impact Of This Research and Disseminationmentioning
confidence: 56%